Brewery heat exchanger networks design and optimization based on pinch analysis at a single ΔT min - Ebrada, Leni C.; De Luna, Mark Daniel G.; Manegdeg, Ferdinand G.; Grisdanurak, Nurak (Philippine Engineering Journal)
Pinch analysis was applied to design and optimize at a single ∆Tmin of 10 oC, a heat exchanger network for maximum energy recovery to reduce the energy consumption of a brewery. At ∆Tmin of 10 oC, the minimum heating and cooling requirements of the brewery were 5,185 kW and 3,039 kW, respectively. Above pinch, 120 possible design configurations were identified but only 8 are feasible. Below pinch, only 7 design configurations are feasible out of 52 possible. The optimum heat exchanger network obtained for the brewery is 1 process-to-process heat exchanger and 8 process-to-utility heat exchangers as a consequence of combining the configurations of the least cost feasible designs for both above and below pinch. The optimum heat exchanger network corresponds to a maximum of 22% heat recovery potential which accounts to 4.5% less than the existing operating cost equivalent to USD432,133 per year at total annualized cost. Other values of ∆Tmin are recommended to be considered for future studies.